Land transfers and "tutorat" relationship in West Africa. Changes and current issues - (:unkn) unknown (My University, 2006)
The paper is a personal synthesis of a collective research on changes in customary land transfers in Benin, Burkina Faso, Côte d'Ivoire et Mali. Far from leading gradually to land market, the individualisation and monetarisation of tutorat relationship between autochthons and migrant farmers does not eradicate the collective and socio-political dimension of strangers' integration, but add another layer to the process of access to land. That makes happen more conflicting situations in the current context of most of the West African countrysides.
Keywords: African Research